2017
DOI: 10.3847/1538-3881/aa7c1d
|View full text |Cite
|
Sign up to set email alerts
|

H i in Virgo’s “Red and Dead” Dwarf Ellipticals—A Tidal Tail and Central Star Formation

Abstract: We investigate a sample of three dwarf elliptical galaxies in the Virgo Cluster that have significant reservoirs of H I. We present deep optical imaging (from CFHT and KPNO), H I spectra (Arecibo), and resolved H I imaging (VLA) of this sample. These observations confirm their H I content and optical morphologies, and indicate that the gas is unlikely to be recently accreted. The sample has more in common with dwarf transitionals, though dwarf transitionals are generally lower in stellar mass and gas fraction.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…Conselice et al 2013; see Sanchez Almeida 2014 for a review). Observations that may indicate cold gas accretion include streams of HI gas surrounding M31 (Thilker et al 2004), HI in red early-type dwarf galaxies on the outskirts of the Virgo cluster (Hallenbeck et al 2012, but see Hallenbeck et al 2017 for follow-up observations that suggest the HI might not be recently accreted), and an HI envelope surrounding a small extended grouping of galaxies within a void (Beygu et al 2013). At the same time, cold gas is expected to be removed or cut off from galaxies through a variety of physical mechanisms that depend on largescale environment.…”
Section: Introductionmentioning
confidence: 99%
“…Conselice et al 2013; see Sanchez Almeida 2014 for a review). Observations that may indicate cold gas accretion include streams of HI gas surrounding M31 (Thilker et al 2004), HI in red early-type dwarf galaxies on the outskirts of the Virgo cluster (Hallenbeck et al 2012, but see Hallenbeck et al 2017 for follow-up observations that suggest the HI might not be recently accreted), and an HI envelope surrounding a small extended grouping of galaxies within a void (Beygu et al 2013). At the same time, cold gas is expected to be removed or cut off from galaxies through a variety of physical mechanisms that depend on largescale environment.…”
Section: Introductionmentioning
confidence: 99%
“…In low density environments, the HI gas in dEs could result from interactions with a companion or a gas accretion from the intergalactic medium (Grossi et al 2009). At most a dozen of HI-bearing dEs have been reported in the outskirts the Virgo cluster (Conselice et al 2003;di Serego Alighieri et al 2007;Hallenbeck et al 2012Hallenbeck et al , 2017, and a couple were observed in low density environments (Grossi et al 2009). With an HI line detection for 42 dEs, our sample is significantly larger than the ones previously reported.…”
Section: Dwarf Ellipticalsmentioning
confidence: 69%
“…Most of the optical studies of HI-bearing dwarf galaxies report blue colors caused by recent star formation activity (Grossi et al 2009;Cannon et al 2011;Huang et al 2012;Honey et al 2018). However, some studies have detected HI in red dEs located in the Virgo cluster (Conselice et al 2003;Hallenbeck et al 2017). In Figure 4, we show the color-magnitude relation for the Galactic extinction 5 corrected g−i and g−r colors of the MATLAS dwarfs present in the regions of the sky observed by either ALFALFA and ATLAS 3D HI survey.…”
Section: Dwarfs Colorsmentioning
confidence: 97%
See 1 more Smart Citation
“…The second caveat is that, even though it is an indicator of a disturbance, the magnitude of the velocity offset between the Hi and optical is much larger than might be expected. Local galaxies have been shown (Oosterloo & van Gorkom 2005;Chung et al 2007;Koopmann et al 2008;Leisman et al 2016;Hallenbeck et al 2017;Minchin et al 2019;Taylor et al 2020) to usually have only a small fraction of their Hi present in their tails, and retain the bulk of their gas in close proximity to their optical discs. Here, the velocity offsets (200-400 km s −1 ) are high enough that the gas may have been entirely displaced from the parent galaxy.…”
Section: Ram-pressure Strippingmentioning
confidence: 99%